The prebiotic and anti-fatigue effects of hyaluronan - Huang, Guoxin; Su, Lu; Zhang, Ni; Han, Ruixuan; Leong, Wai Kit; Li, Xiaoang; Ren, Xuecong; Hsiao, W. L. Wendy (Frontiers in Nutrition, 2022)
Hyaluronan (HA) is a mucopolysaccharide that naturally exists in all living organisms as the main component of the extracellular matrix. Over the last 30 years, HA has been used as the main ingredient in cosmetic products, eye drops, and medicinal products. It is also taken orally as a health supplement. However, the physiological effect of the ingested HA is not clear. In the current study, the interaction between HA and gut microbiota, and the potential prebiotic effects will be investigated. HA was used to treat the C57BL/6 mice for 14 consecutive days, then fecal genomic DNA at this was extracted for 16S rRNA amplicon sequencing. The results showed that HA could significantly change the composition of gut microbiota (GM), e.g., increased the relative abundance of beneficial bacteria, including short-chain fatty acids (SCFAs)-producing bacteria and xylan/cellulose-degrading bacteria, whereas decreased the relative abundance of potential pathogens including sulfate-reducing bacteria (SRB), inflammation and cancer-related bacteria. The rotarod test was used to evaluate the anti-fatigue of HA in the C57BL/6 mice model. And the results showed that HA could lengthen the latency on the accelerating rotarod equipment of the mice. HA increased the concentration of glycogen and superoxide dismutase (SOD) in mice muscle and liver, whereas decreased the serum concentration of malondialdehyde (MDA). Moreover, the metabolic products of Desulfovibrio vulgaris (MPDV), the model SRB bacteria, showed cytotoxic to H9c2 cardiomyocytes in a dosage-dependent manner. MPDV also induced mitochondrial damage by inducing mitochondrial fragmentation, depolarization, and powerless ATP production. Taken together, HA possesses significant anti-fatigue and prebiotic effects of HA.